Penerapan Prinsip-Prinsip Good Governance dan Penanggulangan Tingkat Kemiskinan Di Kabupaten Aceh Barat - Utami, Ade Putri; Ibrahim, Azharsyah; Adnan, Muhammad (Yayasan Kawanad, 2024)
Good governance plays a crucial role in influencing economic growth in a region, which subsequently contributes to poverty reduction. However, high poverty levels and uneven economic growth can negatively impact local communities. This study examines the effects of transparency, accountability, participation, and equity on poverty alleviation in West Aceh Regency. A mixed-methods approach, combining quantitative and qualitative techniques with a triangulation design, was employed. The study involved 379 respondents who were major recipients of social assistance from three sub-districts: Kaway XVI, Samatiga, and Woyla. Data were collected through questionnaires, and additional insights were obtained from three government officials involved in poverty alleviation efforts at BAPEDDA West Aceh Regency. Data analysis utilized multiple linear regression with SPSS 22. The findings indicate that transparency significantly and positively influences poverty alleviation by ensuring that aid distribution is targeted and effectively managed. Accountability also has a significant positive effect, as it integrates community involvement from planning to program evaluation. Participation contributes positively by aligning programs with local needs and enhancing implementation success. Lastly, equity positively impacts poverty alleviation by promoting fair resource distribution, enabling programs to effectively reach all societal levels, including vulnerable groups.